Facilitators and Barriers to Sustainable Employment After Spinal Cord Injury or Acquired Brain Injury: The Person's Perspective - Karcz, Katarzyna; Schiffmann, Barbara; Schwegler, Urban; Staubli, Stefan; Finger, Monika E. (Frontiers in Rehabilitation Sciences, 2022)
Background: Sustaining employment after initial return to work represents a major challenge for people with a disability. While individuals with acquired brain injury (ABI) and spinal cord injury (SCI) make a prime example for this challenge, the affected persons' view on factors supporting and hindering sustainable employment have rarely been in-depth investigated so far. Purpose: To identify facilitators and barriers to sustainable employment from the perspective of persons with ABI or SCI and to examine their perceived relevance. Methods: Fourteen focus groups and 4 individual interviews were conducted and thematically analysed. Results: Participants reported three strongly interrelated overarching themes of facilitators and barriers to sustainable employment: impairment-related, personal and environmental factors. Among these biopsychosocial factors related to work organization, the most important facilitators of sustainable employment were the environmental factors related to workplace and work organisation. Additionally, having a supportive social environment, both private and at work, followed by the personal factors including ability to self-advocate, communicate and learn how to live with a disability were considered as key facilitators. Injury-related impairments, such as decreased mobility and pain for SCI and fatigue and limited cognitive resources for ABI together with the environmental factors related to insurance procedures and the social security system were reported as the most the influencing barriers. Conclusions: To optimally support sustainable employment of people with SCI or ABI, the biopsychosocial factors identified in the present study as well as their connection should receive particular attention as key targets for interventions in vocational integration practice. The focus should be on the empowerment of those affected as well as on the creation of supportive work environment and work conditions that match the needs and abilities of persons with SCI or ABI.